(untitled) (Canadian Dermatology Today, 2025)
Many patients living with hidradenitis suppurativa (HS) experience a significant impairment in their quality of life. One of the most prominent symptoms in these patients is pain, which makes a major contribution to their overall distress. Despite its impact, pain control has been shown to be an unmet need for many patients. Pain has physical, psychological and social impacts. When poorly controlled, pain can lead to increased visits to emergency departments, a higher likelihood of self-medication, and generally poor disease control. This review provides a clinical approach for managing pain in patients with HS.